On the Fourth Coefficient of Functions in the Carathéodory Class - Kwon, Oh Sang; Lecko, Adam; Sim, Young Jae (Computational methods and function theory, 2018)
In the present paper, a formula for the fourth coefficient of Carathéodory functions was computed.